An Unusual Case of Cirrhosis - Ahmad Alkaddour; Kenneth J. Vega; Adil Shujaat (Case Reports in Gastrointestinal Medicine)
49-year-old white female with remote h/o sarcoidosis was referred to GI when her liver was noted to be nodular. Physical examination revealed normal vital signs and no icterus, spider nevi, clubbing, ascites, hepatosplenomegaly, or ankle edema. LFTs, hepatitis serologies, ANA, AMA, ASMA, Ferritin, Ceruloplasmin, and α1-AT, level were unremarkable. Liver biopsy showed cirrhosis. She developed worsening of baseline SOB and was hospitalized. She was eventually diagnosed with constrictive pericarditis. A diagnosis of cardiac cirrhosis was made.